Development of Science Module based on Flipbook about Physics in the Respiratory System to Improve Students’ Learning Independence - Dwi Agnes Setianingrum; El Minahussaniyyatul Ula; Septania Pratiwi; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
Learning is now gradually recovering from the effects of the COVID-19 pandemic with the start of limited face-to-face learning. This makes educators need to innovate so that students still have independent learning. Less than optimal online learning causes students to be too passive when learning offline. To overcome this, research was carried out through the development of science module based on flipbook about physics in the respiratory system. This study aims to determine the feasibility level of the module, to determine the responses of students, and to find out whether the module can increase students' independence in science learning. This study uses the Thiagarajan 4D (Four-D Model) development model, consisting of four stages, namely the definition stage, the design stage, and the development stage. The dissemination stage was not carried out, this research was only limited to product feasibility testing. This study uses a descriptive qualitative approach. The sample in this study is class VIII A totaling 10 people. The collection technique used is a questionnaire and documentation. The results showed that: (1) science module based on flipbook was feasible, judging from the percentage of the feasibility of the module 96.73% (very feasible), (2) student responses to the module were in the very good category, seen from the percentage of interest in the module 90.00% (very interested), and the students' independence in learning science using flipbook-assisted science modules were included in the high category, with a percentage of 86.25% (high science learning independence).